Simulated Experiment on Wind Erosion Resistance of Salix Residual in the Agro-Pastoral Ecotone - Li, Qiang; Kang, Furen; Zhang, Zheng; Ma, Chunyan; Nan, Weige (Frontiers in Environmental Science, 2021)
Plant residual is an effective way in retarding soil wind erosion in the agro-pastoral ecotone. However, few studies have determined the effects of sand plant residual on wind erosion resistance. Based on field surveys, the influences of Salix residual biomass of 200 g m-2, 400 g m-2, 600 g m-2 and 800 g m-2, soil incorporated with residual thickness of 0.5 cm, 1.0 cm and 2.0 cm, as well as typical proportion of residual branch and leaves (2:1, 1:1 and 1:2) on wind erosion resistance were investigated using a simulated wind tunnel. The results showed that, (1) soil loss amount ranged from 1.56 to 40.8 kg m-2 as Salix residual biomass decreased from 800 to 0 g m-2, with a critical residual biomass value of 400 g m-2.(2) As the thickness of soil incorporated residual increased, soil loss amount reduced rapidly, especially for 0-9cm above the surface accounts for 84.6% of the total. (3) Salix branch residual is more important in resisting soil wind erosion as compared with its leaves. This kind of study may provide theoretical explanations for the optimal reconstruction of sandy vegetation in the northern wind-sand regions.